The information fragmentation problem through dimensions of software, time and personal projects (Informatica, 2015)
This paper is an extended abstract of the doctoral thesis [1]. It presents an overview of the research into the field of Personal Information Management (PIM) and a study of information fragmentation on the three axes: software, time and personal projects. These axes were investigated through three studies: (i) a preliminary investigative study by interviews and observation of project information management, (ii) the observed usage of the purpose-built project information management research prototype, and (iii) logging of the usage of the same prototype in the wild. The  findings show (i) the extensive information fragmentation in each individual PIM tool besides cross-tool fragmentation, (ii) the information overload preventing focusing on the subset of fragmented project related information and changing focus over time, and (iii) the importance of support information (information scraps) and its integration into project flow.